Assessment of fluoride bio-accessibility in early childhood diets - Kronic, Jelena; Duckworth, Ralph M.; Angione, Claudio; Levy, Steven M.; Zohoori, Fatemeh Vida (Frontiers in Oral Health, 2025)
IntroductionCurrently available dietary recommendations for fluoride provided as “adequate intake” (AI) and “tolerable upper intake level” (UL) assume 100% fluoride availability for utilization by the body, which is often not the case. To prevent the development of dental fluorosis, AI and UL values must include fluoride bioavailability. However, the lack of data on fluoride bioavailability/bio-accessibility has hindered progress so far. This study aimed to measure fluoride bio-accessibility of the dietary sources commonly consumed by children below four years of age.MethodsA total of 103 food and meal samples were purchased, prepared, and analyzed for fluoride content, subjected to a standardized static in vitro digestion procedure and subsequent determination of fluoride concentration of resultant mixtures necessary for the final fluoride bio-accessibility calculation. Fluoride concentrations before and after in vitro digestion were determined directly using a fluoride-ion-selective electrode after addition of TISAB III, or indirectly by an acid diffusion method. Additionally, fluoride concentration of milk samples was determined using a combination of microwave-assisted acid digestion and the direct method of fluoride analysis.ResultsMean (SD) fluoride bio-accessibility for individual food samples was 44.7% (37.5%). The mean (SD) fluoride bio-accessibilities for meals created with juice, carbonated drinks, tap water, and milk were 79.0% (21.9%), 64.3% (20.7%), 40.2% (20.9%), and 71.5% (17.1%), respectively. For the rest of the meals with no common mixing agent, the mean (SD) fluoride bio-accessibility was 50.8% (55.9%).ConclusionThe majority of dietary sources analyzed in this project resulted in fluoride bio-accessibilities below 100%, indicating incomplete utilization of consumed fluoride. As the first study of its kind, these findings represent a critical initial step for future research and provide valuable insights to inform policymakers and health authorities in revising fluoride intake guidelines.